2014
DOI: 10.1016/j.devcel.2014.02.013
|View full text |Cite
|
Sign up to set email alerts
|

The Centrosome-Specific Phosphorylation of Cnn by Polo/Plk1 Drives Cnn Scaffold Assembly and Centrosome Maturation

Abstract: SummaryCentrosomes are important cell organizers. They consist of a pair of centrioles surrounded by pericentriolar material (PCM) that expands dramatically during mitosis—a process termed centrosome maturation. How centrosomes mature remains mysterious. Here, we identify a domain in Drosophila Cnn that appears to be phosphorylated by Polo/Plk1 specifically at centrosomes during mitosis. The phosphorylation promotes the assembly of a Cnn scaffold around the centrioles that is in constant flux, with Cnn molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
308
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(319 citation statements)
references
References 51 publications
9
308
2
Order By: Relevance
“…Raff and colleagues recently showed that Plk1 phosphorylates Cnn at its phosphoregulated-multimerization (PReM) domain, which allows Cnn to multimerize and assemble a scaffold around centrioles. Because multimerized Cnn is localized in very close proximity to the centrioles and diffuses from there throughout the entire PCM, this Cnn-mediated scaffold helps to anchor the PCM and thus facilitates centrosome maturation (Conduit et al, 2014). Consistently, the lack of Cnn induces mitotic defects owing to an unstable linkage between centrioles and PCM (Conduit et al, 2010;Lucas and Raff, 2007).…”
Section: Plk1 Functions In Centrosome Maturation and Spindle Formationmentioning
confidence: 57%
See 1 more Smart Citation
“…Raff and colleagues recently showed that Plk1 phosphorylates Cnn at its phosphoregulated-multimerization (PReM) domain, which allows Cnn to multimerize and assemble a scaffold around centrioles. Because multimerized Cnn is localized in very close proximity to the centrioles and diffuses from there throughout the entire PCM, this Cnn-mediated scaffold helps to anchor the PCM and thus facilitates centrosome maturation (Conduit et al, 2014). Consistently, the lack of Cnn induces mitotic defects owing to an unstable linkage between centrioles and PCM (Conduit et al, 2010;Lucas and Raff, 2007).…”
Section: Plk1 Functions In Centrosome Maturation and Spindle Formationmentioning
confidence: 57%
“…In addition to initiating centrosome maturation, Plk1 also plays a crucial role in stabilizing the link between the PCM and centrioles by phosphorylating Cnn (the D. melanogaster homolog of mammalian CDK5RAP2) (Conduit et al, 2014). Raff and colleagues recently showed that Plk1 phosphorylates Cnn at its phosphoregulated-multimerization (PReM) domain, which allows Cnn to multimerize and assemble a scaffold around centrioles.…”
Section: Plk1 Functions In Centrosome Maturation and Spindle Formationmentioning
confidence: 99%
“…This may vary a little among different cell types, as in the embryo, Conduit and colleagues suggest that Asl initially helps recruit Spd-2, which, in turn, recruits CNN. CNN, on the other hand, was not required to recruit Asl or Spd-2, but was required to maintain Spd-2 in the PCM (Conduit et al 2014a). CNN mutants show reduced g-tubulin and Aurora A at the embryonic centrosome (Megraw et al 1999;Zhang and Megraw 2007), and a conserved motif near the amino terminus of CNN has been identified as essential for recruitment of g-tubulin, D-TACC (transforming acidic coiled-coil proteins), and the Ch-TOG family microtubule polymerase Msps (Minispindles) (Zhang and Megraw 2007).…”
Section: Pcm Assemblymentioning
confidence: 99%
“…3C) (Fu and Glover, 2012;Lawo et al, 2012;Mennella et al, 2012;Sonnen et al, 2012). Both PCNT and CDK5RAP2 (Cnn in Drosophila) modulate the PCM expansion; when the amount of either protein is increased, the size of the PCM increases (Loncarek et al, 2008;Lawo et al, 2012;Conduit et al, 2014;Megraw et al, 1999). These studies suggest that these components modulate the dynamics of the PCM.…”
Section: Morphology Of the Pericentriolar Materialsmentioning
confidence: 99%